Arquitetura de controle em tempo real para redes de distribuição com geração fotovoltaica e sistemas de armazenamento de energia em baterias - Parqui, Wilson Omar Ramos (2025)
The rapid expansion of photovoltaic generation in distribution networks delivers environmental and operational gains but heightens voltage-control challenges in the face of solar intermittency. To address these challenges, this dissertation proposes, develops, and validates in real time a cyber-physical co-simulation methodology that integrates Typhoon HIL and OpenDSS. The approach encompasses detailed modeling of the network and distributed energy resources, the parameterization and implementation of control strategies, and experimental validation in an HIL environment. Additionally, it incorporates a metaheuristic optimization stage in which a PSO-based algorithm determines the optimal allocation of BESS, identifying the buses that maximize technical performance in terms of voltage profile and electrical losses. The strategies evaluated include Volt-VAr control in photovoltaic inverters and cooperative active-power management of the BESS. Validation on the IEEE-34 feeder considered two scenarios: a 1,800-s dynamic test to capture responses to abrupt variations in load and generation, and a 24-h simulation for a global performance assessment. The results show that coordinating these strategies together with the optimal allocation of BESS mitigates voltage-limit violations, maintains levels within regulatory limits, reduces losses, and enhances system flexibility and operational stability.